Simulators and training models for diagnostic and therapeutic gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Technical and Technology Review - Coluccio, Chiara; Jacques, Jérémie; Hritz, Istvan; Boskoski, Ivo; Abdelrahim, Mohamed; Bove, Vincenzo; Cunha Neves, João A.; de Jonge, Pieter J. F.; Dell’Anna, Giuseppe; Esposito, Gianluca; Facciorusso, Antonio; Gincul, Rodica; Giuffrida, Paolo; Kalapala, Rakesh; Kapizioni, Christina; Longcroft-Wheaton, Gaius; Nagl, Sandra; Tziatzios, Georgios; Voiosu, Theodor; Dray, Xavier; Barbieri, Bridget; Gralnek, Ian M.; Fuccio, Lorenzo (Endoscopy, 2025)
Gastrointestinal (GI) endoscopy comprises both diagnostic and therapeutic procedures involving the luminal GI tract as well as the biliary tree, liver, and pancreas. GI endoscopy is challenging to learn, requiring both cognitive (nontechnical) and technical skills, and requires extensive practice to attain proficiency. Simulation-based training has been shown to assist trainees and young endoscopists in acquiring new skills and accelerating the learning curve. Moreover, simulation-based training creates an ideal environment for trainees to initially learn and practice skills while making mistakes with no risk to patients.This review, divided in two parts, offers a comprehensive summary of the different classes of simulators available for GI endoscopic training.In Part I, only mechanical simulators are reported and described. In Part II, animal simulators (ex vivo/in vivo) and virtual reality models are detailed, together with prototypes that are currently not commercially available.